Various Applications of Tofacitinib and Ruxolitinib (Janus Kinase Inhibitors) in Dermatology and Rheumatology: A Review of Current Evidence and Future Perspective - Sara Sadeghi; Azadeh Goodarzi (Mattioli1885, 2022)
Backgrounds: Janus kinase inhibitors (JAKi) are anti-inflammatory medications suppressing Janus kinase-signal transducer and activator of transcription (JAK-STAT) pathway by inhibiting various cytokines receptors on the membrane of cells. Mutations and polymorphisms on JAK and STAT proteins can cause dysregulation in the balance of immune system, and ultimately result in autoimmune disorders. Objectives: to record and summarize the overall efficacy and safety of JAKi in various autoimmune conditions such as alopecia areata (AA), psoriasis vulgaris (PV), psoriatic arthritis (PsA), atopic dermatitis (AD), vitiligo, hidradenitis suppurative (HS), lichen planus (LP), and pyoderma gangrenosum (PG). Methods: A thorough review of articles was performed across PubMed and Google Scholar on meta-analyses, systematic reviews, clinical trials and case studies evaluating the treatment of autoimmune disorders such as AA, PV, PsA, AD, vitiligo, LP, HS, and PG with JAKi. Duplicated data and animal experiments or in vitro/ex vivo studies were excluded. Results: all the reviewed articles reported beneficial effects of tofacitinib and ruxolitinib application in the treatment of disorders mentioned above with the autoimmune predisposition. Conclusion: tofacitinib and ruxolitinib showed potential efficacy in treating several autoimmune disorders. Based on records in the reviewed studies, both medications had acceptable safety profiles; however, physicians are recommended to outweigh the risks and benefits of such treatments for each specific condition.